A fine balance : a novel - Mistry, Rohinton, 1952- (New York : Vintage Books, 1997)
A portrait of India featuring four characters. Two are tailors who are forcibly sterilized, one is a student who emigrates, and the fourth is a widowed seamstress who decides to hang on. A tale of cruelty, political thuggery and despair by an Indian from Toronto, author of Such a Long Journey.
"First published in the United States in hardcover by Alfred A. Knopf, Inc., New York, in 1996."
Accelerated Reader AR
Keywords: Apartment houses -- Fiction; City and town life -- Fiction; Historical fiction; Domestic fiction; India -- History -- 1947- -- Fiction